Tinjauan Fiqih Empat Mazhab Terhadap Acara Walimah - M. Dzikrullah Faza (Al Fuadiy Jurnal Hukum Keluarga Islam, 2022)
: In Islamic fiqh Walimah can be interpreted specifically and generally. The general meaning for Walimah is any celebratory event that involves many people. While in a special meaning called walimatul al-ursy or walimah marriage is interpreted by the inauguration of the wedding which aims to inform other audiences that the bride and groom have officially become legal husband and wife, as well as as gratitude for the marriage of the two. There are many things in walimah and its provisions that every Muslim must understand, in order to avoid the fallacy of the provisions of Islamic law. Therefore, islamic fiqh puts provisions in this case. This article, aims to examine and analyze the views of the four Mazhab in the case of walimah whether walimah marriage or others walimah and the matters contained therein also include the postulates of each opinion as well as discuss them using descriptive methods of analysis. The results of this analysis show that the dalil of the walimah of marriage is sunnah stronger in its postulate than the dalil of wajib and the dalil of attending the obligatory marriage walimah is easier to accept and stronger than the dalil opinions of the Sunnah and fardhu kifayah, and the walimah time starts from the akad until the indefinite time even though it has been divorced or died. Can also be done with any food or drink without any certain levels